Callus induction and adventitious shoot regeneration in two genotypes of sweet cherry (Prunus avium) - Peer, F A; Rather, Z A; Mir, M A; Bhat, K M; Dar, K R; Hussain, G (The Indian Journal of Agricultural Sciences, 2012)
Studies were carried out during 2006–09 with two genotypes of sweet cherry–Mazzard (rootstock) and Bigarreau Noir Grossa (commercial cultivar) for developing adventitious shoot propagation protocol using in vitro leaf segments as explants. MS medium supplemented with BAP + 2,4-D (0.50 + 2.0 mg/l) resulted in maximum callus initiating cultures (66.19%) with maximum callus fresh weight (2.85 g). Highest adventitious shoot initiating cultures (32.74%) with maximum shoot number/culture (9.71) was recorded with BAP + NAA (2.0 + 1.0 mg/l). Adventitious shoots (10 mm or more) cultured in root induction medium (MS medium supplemented with IBA) were incubated under darkness for 10 days and then transferred to root development medium (hormone-free MS medium) under normal incubation conditions of culture room (16/8 hr photoperiod, 24±1 oC temperature, 40±3 mol/m2/s light intensity using 40 W fluorescent tubes). Maximum rooting in microshoots (36.15%) with maximum number of roots/shoot (9.58) were recorded with IBA (2.5 mg/l). Among the two genotypes, Mazzard proved superior to Bigarreau Noir Grossa with respect to all shoot and root regeneration parameters.